Autofluorescence identifies highly phagocytic tissue-resident macrophages in mouse and human skin and cutaneous squamous cell carcinoma - Bourdely, Pierre; Petti, Luciana; Khou, Sokchea; Meghraoui-Kheddar, Aida; Elaldi, Roxane; Cazareth, Julie; Mossadegh-Keller, Noushine; Boyer, Julien; Sieweke, Michael H.; Poissonnet, Gilles; Sudaka, Anne; Braud, Veronique M.; et al. (Frontiers in Immunology, 2022)
Macrophages from human and mouse skin share phenotypic and functional features, but remain to be characterized in pathological skin conditions. Skin-resident macrophages are known to derive from embryonic precursors or from adult hematopoiesis. In this report, we investigated the origins, phenotypes and functions of macrophage subsets in mouse and human skin and in cutaneous squamous cell carcinoma (cSCC) using the spectral flow cytometry technology that enables cell autofluorescence to be considered as a full-fledged parameter. Autofluorescence identifies macrophage subsets expressing the CD206 mannose receptor in human peri-tumoral skin and cSCC. In mouse, all AF+ macrophages express the CD206 marker, a subset of which also displaying the TIM-4 marker. While TIM-4-CD206+ AF+ macrophages can differentiate from bone-marrow monocytes and infiltrate skin and tumor, TIM-4 identifies exclusively a skin-resident AF+ macrophage subset that can derive from prenatal hematopoiesis which is absent in tumor core. In mouse and human, AF+ macrophages from perilesional skin and cSCC are highly phagocytic cells contrary to their AF- counterpart, thus identifying autofluorescence as a bona fide marker for phagocytosis. Our data bring to light autofluorescence as a functional marker characterizing subsets of phagocytic macrophages in skin and cSCC. Autofluorescence can thus be considered as an attractive marker of function of macrophage subsets in pathological context.